Dampak Kekerasan Pada Anak - Azizi, Muhammad Firlian (CV WAHANA PUBLIKASI, 2022)
Violence is a form of action that tends to be physical which causes injury, pain or something that requires attention, namely coercion or unwillingness of the injured party. Violence can be carried out using physical means, resulting in children suffering from injuries from being hit, throwing hard objects, and much more. Psychologically, children will experience the formation of bad attitudes in themselves, namely difficulty focusing, difficulty sleeping, eating disorders, and a tendency to hurt themselves. Some violence against children occurs in the child's own home, school, and in the environment where the child interacts. To prevent violence against children, this can be done by paying attention, supervising and caring for children correctly and diligently. The government needs to make a law about violence against children and punish perpetrators of violence against children to make them aware of what they are doing. The purpose of this research is to illustrate the impact of violence on children and how to prevent it. This research was carried out using normative juridical (normative legal research methods) which was carried out using journals and books.